2021
DOI: 10.1002/jdd.12623
|View full text |Cite
|
Sign up to set email alerts
|

Is food insecurity a barrier to dental student success?

Abstract: Purpose The prevalence of food insecurity among undergraduate students is higher than the national average and associated with adverse academic outcomes. Our objective was to describe the prevalence of food insecurity, food access behaviors, and associations between food security status and well‐being in a dental student population. Methods All dental students (N = 328) enrolled in the College of Dentistry at the University of Iowa in the fall 2019 semester were invited to participate. The survey was designed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 16 publications
(46 reference statements)
0
14
0
Order By: Relevance
“…35 Unfortunately, similar to our dental students with food insecurity, multiple investigators have reported that food banks and other programs are not well utilized by undergraduate students. 13,19,20,35 Students with food insecurity report associating food bank use with a stigma, embarrassment, and/or shame, as well as pragmatic concerns associated with lack of transportation, hours of operation, and insufficient time. 35 Students from lower socioeconomic backgrounds benefit from free and/or reduced breakfast and lunch programs during elementary and secondary school; free and/or reduced meal programs are not available to university students regardless of socioeconomic background.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…35 Unfortunately, similar to our dental students with food insecurity, multiple investigators have reported that food banks and other programs are not well utilized by undergraduate students. 13,19,20,35 Students with food insecurity report associating food bank use with a stigma, embarrassment, and/or shame, as well as pragmatic concerns associated with lack of transportation, hours of operation, and insufficient time. 35 Students from lower socioeconomic backgrounds benefit from free and/or reduced breakfast and lunch programs during elementary and secondary school; free and/or reduced meal programs are not available to university students regardless of socioeconomic background.…”
Section: Discussionmentioning
confidence: 99%
“…11,21 Novel demographic questions (e.g., food procurement) were developed in a reiterative process. 20 The validated USDA's ten item Adult Food Security Module was used to assess food security status. 22 Students were classified as food secure if they answered "no" to all questions and food insecure if they answered "yes" to one or more questions.…”
Section: Survey Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Data were descriptively analyzed to assess change in food security status. We employed a twosided Fisher Exact Test of Independence (Marshall et al, 2021) to test our hypotheses that changes in student food security status during the pandemic are associated with intersecting identities. The analysis was completed with RStudio (posit.co).…”
Section: Survey Itemsmentioning
confidence: 99%